Critical amino acids in Escherichia coli UmuC responsible for sugar discrimination and base-substitution fidelity - Vaisman, Alexandra (Oxford University Press, 2012)
The active form of Escherichia coli DNA polymerase V responsible for damage-induced mutagenesis is a multiprotein complex (UmuD′(2)C-RecA-ATP), called pol V Mut. Optimal activity of pol V Mut in vitro is observed on an SSB-coated single-stranded circular DNA template in the presence of the β/γ complex and a transactivated RecA nucleoprotein filament, RecA*. Remarkably, under these conditions, wild-type pol V Mut efficiently incorporates ribonucleotides into DNA. A Y11A substitution in the ‘steric gate’ of UmuC further reduces pol V sugar selectivity and converts pol V Mut into a primer-dependent RNA polymerase that is capable of synthesizing long RNAs with a processivity comparable to that of DNA synthesis. Despite such properties, Y11A only promotes low levels of spontaneous mutagenesis in vivo. While the Y11F substitution has a minimal effect on sugar selectivity, it results in an increase in spontaneous mutagenesis. In comparison, an F10L substitution increases sugar selectivity and the overall fidelity of pol V Mut. Molecular modeling analysis reveals that the branched side-chain of L10 impinges on the benzene ring of Y11 so as to constrict its movement and as a consequence, firmly closes the steric gate, which in wild-type enzyme fails to guard against ribonucleoside triphosphates incorporation with sufficient stringency.